Comprehensive approach to skin ulcers caused by calciphylaxis in a patient with chronic renal failure, treated with topical sodium thiosulfate ointment: A case report (2025)
Purpose: This clinical case report aims to document the successful management of calcific arteriolopathy, also known as calciphylaxis, in a 74-year-old male patient with multiple comorbidities, including chronic kidney disease. The primary objectives were to highlight the effectiveness of a multidisciplinary approach –particularly the use of topical sodium thiosulfate– and to demonstrate the positive impact on glomerular filtration rate (GFR) following wound healing. Methods: The patient presented with two ulcers on the posterior aspect of the right leg, which developed after hospitalization for congestive heart failure. A comprehensive treatment strategy was employed, involving multiple medical specialties, including infectious disease, nephrology, and dermatology. Treatment included intravenous antibiotics, pain management, transitioning to new-generation anticoagulants, and the use of a unique ointment containing sodium thiosulfate for wound care. Results: After seven months, the patient achieved complete wound healing, and his glomerular filtration rate improved significantly. Three consecutive measurements of renal filtration parameters confirmed this positive impact. The topical application of sodium thiosulfate played a crucial role in wound healing, highlighting its potential as a treatment option for calciphylaxis. Conclusion: This case underscores the importance of interdisciplinary management in calcific arteriolopathy, addressing both underlying causes and localized wound care. The successful outcome and improved renal function following wound healing suggest that topical sodium thiosulfate can be a valuable treatment approach, particularly when systemic therapy is challenging. This report contributes to the limited literature on the topical use of sodium thiosulfate in calciphylaxis and emphasizes the need for comprehensive care in patients with this condition.